Perbedaan Penggunaan Active Birth dengan Metode Birthball dan Hypnobirthing terhadap Lama Inpartu Kala I - Ika Yulia Darma; Meldafia Idaman; Silvi Zaimy; Riri Yulia Handayani (Universitas Batanghari Jambi, 2021)
Childbirth is a physiological process. In women giving birth, the time span is marked by uterine contractions characterized by pain, regularity, cervical dilatation and cervical effacement. One method of using active birth that has been carried out in Indonesia is the use of birth balls and hypnobirthing as a form of effort to provide maternal care in helping the birth process with evidence base The purpose of this study was to study the differences in the use of active birth with birthball and hypnobirthing methods on the length of the first stage of labor. This type of research is a quasi-experimental with a cross-sectional approach, the research design is Posttest Only Design. The research was conducted in May - December 2020 at the Independent Practice Midwife in Padang City. The sample of this study were primiparous mothers who had gestational age at term (37-42 weeks) and had no complications. The sampling technique used is non-probability sampling, namely purposive sampling. The sample is 20 people, with 10 samples using the birthball technique and 10 samples using the hypnobirthing technique. Data were obtained by using observation sheets. Data were analyzed by univariate and bivariate. Statistical test using Mann-Whitney test. The results showed that the average length of labor in the first stage using birthball was 3.15 ± 0.29 and the average length of labor in the first stage using hypnobirthing was 3.55 ± 0.27. The difference in the mean length of the first stage of labor between the 2 groups was 0.40. the results of statistical tests using the Mann Whitney test obtained p value 0.000 (p 0.05) which means that there is a significant difference in the use of active birth with the birthball method and hypnotherapy for the first stage of labor. It can be concluded that the difference in the the use of active birth with birthball and hypnobirthing methods on the length of the first stage of labor.